Intravenous Immunoglobulin G (IVIG) Need Assessment Survey Toward Local Manufacturing of IVIG Using a Mini-Pool Plasma Fractionation Technique - Bisrat Bekele; Zekarias Masresha; Mekdelawit Alemayehu; Berhanu Seyoum; Liya Wassie; Markos Abebe (SAGE Publishing, 2023)
Immunoglobulin therapy has a crucial role in the treatment of primary and secondary immunodeficiencies as well as in a multitude of neurologic, hematologic, infectious, and autoimmune conditions. In the current study, a preliminary pilot scale needs assessment survey was conducted to examine the need for IVIG among patients in Addis Ababa, Ethiopia, and in so doing justify local manufacturing of IVIG products. The survey was performed by administering a structured questionnaire to private and government hospitals, a national blood bank, a regulatory body, and healthcare researchers working in academia and pharmaceutical companies. The questionnaire encompassed demographics and specific IVIG-related questions designed for each institution. Responses supplied in the study provide qualitative data. Our findings indicated that IVIG has been registered by the regulatory body for use in Ethiopia and there is a demand for the product in the country. The study also highlights that patients go as far as to clandestine markets to procure IVIG products at a cheaper price. To impede such illegal routes and make the product readily accessible, a small-scale and low-cost approach such as a mini-pool plasma fractionation technique could be implemented to locally purify and prepare IVIG using plasma collected through the national blood donation program.